211k views
2 votes
Factor-8x^3-2x^2-12x-3 by grouping

User Dieterg
by
5.2k points

1 Answer

4 votes

Answer:


=-\left(4x+1\right)\left(2x^2+3\right)

Explanation:


-8x^3-2x^2-12x-3\\\mathrm{Factor\:out\:common\:term\:}-1\\=-\left(8x^3+2x^2+12x+3\right)\\\mathrm{Factor}\:8x^3+2x^2+12x+3:\quad \left(4x+1\right)\left(2x^2+3\right)\\8x^3+2x^2+12x+3\\=\left(8x^3+2x^2\right)+\left(12x+3\right)\\\mathrm{Factor\:out\:}3\mathrm{\:from\:}12x+3\mathrm{:\quad }3\left(4x+1\right)\\12x+3\\\mathrm{Rewrite\:}12\mathrm{\:as\:}3\cdot \:4\\=3\cdot \:4x+3\\\mathrm{Factor\:out\:common\:term\:}3\\=3\left(4x+1\right)


\mathrm{Factor\:out\:}2x^2\mathrm{\:from\:}8x^3+2x^2\mathrm{:\quad }2x^2\left(4x+1\right)\\8x^3+2x^2\\\mathrm{Apply\:exponent\:rule}:\quad \:a^(b+c)=a^ba^c\\x^3=xx^2\\=8xx^2+2x^2\\\mathrm{Rewrite\:}8\mathrm{\:as\:}2\cdot \:4\\=2\cdot \:4xx^2+2x^2\\\mathrm{Factor\:out\:common\:term\:}2x^2\\=2x^2\left(4x+1\right)\\=3\left(4x+1\right)+2x^2\left(4x+1\right)\\\mathrm{Factor\:out\:common\:term\:}4x+1\\=\left(4x+1\right)\left(2x^2+3\right)\\=-\left(4x+1\right)\left(2x^2+3\right)

User Matteeyah
by
4.7k points